2016
DOI: 10.15761/jts.1000129
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D deficiency, cellular hypoxia, and caspase-3 with renal disease in pediatric diabetic nephropathy

Abstract: The increased prevalence of Type I Diabetes (T1D) has also led to an increase in the number of macro-and microvascular complications of diabetes such as coronary heart disease, stroke, visual impairment, diabetic nephropathy (DN), and end stage renal disease (ESRD). Additionally, diabetes remains the most common reason for progressing to end stage renal disease.The aim of the study was to investigate the level of hypoxic disorders, condition of apoptosis controlling system and Vitamin D3 levels in children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…At the same time, these patients have normal BP values and increased serum ET-1 levels. In our previous studies [ 21 , 22 ] we found that patients with T1D have high levels of intracellular hypoxia (HIF-1alfa, marker) and apoptosis effectors. We hypothesise that increased GFR might be a response to metabolic changes that have a case in T1D, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, these patients have normal BP values and increased serum ET-1 levels. In our previous studies [ 21 , 22 ] we found that patients with T1D have high levels of intracellular hypoxia (HIF-1alfa, marker) and apoptosis effectors. We hypothesise that increased GFR might be a response to metabolic changes that have a case in T1D, i.e.…”
Section: Discussionmentioning
confidence: 99%